Balancing ecosystem services supply-flow-demand for watershed ecological security: a case study of the Hai River Basin, China - Rong, Yuejing; Zheng, Lifu; Zhao, Yu (Frontiers in Ecology and Evolution, 2025)
Water ecological security plays a crucial role in watershed management for sustainable development and social stability. For a watershed’s ecological security, the effective matching of the supply and demand of water-related ecosystem services and the complex trade-offs among different services are essential. This study is centered on China’s water-scarce Haihe River Basin, aiming to contribute to the basin’s ecological security by exploring strategies to balance service supply and demand and enhance synergies. This study investigated and assessed the dynamic supply–demand relationship of water-related ecosystem services in the Haihe River Basin. It analyzed the evolution law of service flow and quantified the trade-offs between different services to identify strategies for balancing supply and demand, maintaining a stable flow, and exploring management interventions.The results show that: (1) Over the past 20 years, the supply of water conservation service (WCS) and soil conservation service (SCS) increased overall but declined locally. WCS declined in the Yongding River Basin and parts of the North China Plain, while SCS decreased in the Yanshan Mountains and the North China Plain. WCS demand dropped in 40% of the basin (the Plain), and SCS demand remained high in mountainous areas due to erosion. (2) High-value areas of WCS flow are in the Zhangwei River Basin’s mountain–plain transition zone, SCS flow in the North China Plain, and Water Purification Service (WPS) in high-altitude mountain areas. WPS shows insufficient flow, which hinders the supply–demand balance. (3) In supply–demand matching respects, the deficit area of WCS expanded because of high water demand in human-activity-intensive areas. SCS has supply-demand imbalances in both mountains and plains, and WPS shows a serious basin-wide deficit. (4) In Service trade-offs respects, WCS and SCS maintain a strong correlation (R≥0.90). The synergy between WCS and WPS changed due to agricultural pollution and riparian degradation. There is no significant correlation between SCS and WPS. Therefore, the innovation of this study lies in focusing on the supply–demand matching and spatial trade-offs of services in watershed ecological security. The findings offer valuable insights for optimizing water ecosystem management practices and informing policy decisions. By understanding these relationships and trade-offs, appropriate management interventions can be designed to mitigate negative trade-offs and enhance synergies, ultimately achieving the watershed ecological security.